КАМОЛОТ ТИЗИМИДА ПСИХОЛОГИК ҲИМОЯ (назарий ёндашув) - Садриддинов, С.Р. (SCIENCE and SOCIETY, 2018)
Psychological protection serves to overcome the psychological discomfort of the individual and is divided into basic and acquired psychological defenses. Psychological protection manifests itself in a certain form of behavior, and its essence is determined by the presence of psychological culture and life experience, including the successful socialization of the subject.